Respuesta :

Answer:

[tex]\frac{4}{\sqrt{7}}-1+\frac{2}{\sqrt{7}}+1[/tex]

[tex]=\frac{4}{\sqrt{7}}+\frac{2}{\sqrt{7}}-1+1[/tex]

[tex]\frac{4}{\sqrt{7}}+\frac{2}{\sqrt{7}}=\frac{6\sqrt{7}}{7}[/tex]

[tex]\frac{6\sqrt{7}}{7}-1+1[/tex]

[tex]-1+1=0[/tex]

[tex]=\frac{6\sqrt{7}}{7}[/tex]

OAmalOHopeO

Answer:

Answer is (6[tex]\sqrt{7}[/tex] +2)/6

Step-by-step explanation:

The question isn't very clear, so I'm gonna assume the denominator is  [tex]\sqrt{7}[/tex]-1 and [tex]\sqrt{7}[/tex]+1

Ver imagen rajavamsi566
ACCESS MORE